Spontaneous Pneumomediastinum in a Young Gentleman - SOIB, AHMAD SYAFIQ; SAHAR, MOHD AZMANI; AB RAHMAN, SITI SORAYA; FAZEL, MUHAMMAD FATTAH (Malaysian Journal of Science Health & Technology, 2022)
Spontaneous pneumomediastinum (SPM) is defined as presence of free air or gas in the mediastinum. It may occur in young healthy individuals without serious underlying lung disease. SPM is a rare presentation at the Emergency Department; it typically occurs among tall and thin individuals. We report a case of spontaneous pneumomediastinum in a gentleman who presented with a short history of chest and neck pain after coming back from work. Neck radiograph showed neck subcutaneous emphysema and chest radiograph showed pneumomediastinum with no evidence of pneumothorax or rib fracture.